Inflationary attractors and perturbation spectra in generally coupled gravity - Amendola, Luca; Bellisai, Diego; Occhionero, Franco (Arxiv, 1993)
A generic outcome of theories with scalar-tensor coupling is the existence of inflationary attractors, either power-law or de Sitter. The fluctuations arising during this phase are Gaussian and their spectrum depends on the wavenumber $k$ according to the power-law $k^{1/(1-p)}$, where
Gesehen am 21.11.2017